Dynamic image processing and 3D reconstruction for medical applications - Huang, Yan. (2009)
The goal of medical image processing in this thesis is to extract information from 2D retinal blood vessel morphology which has potential applications for 3D reconstruction of vessel structure and clinical study of diseases. However, images acquired from medical imaging instruments are largely characterized by high noise and dynamic in nature. In this research, multiple focused 2D planes are acquired to study the characteristics of the 3D vessel structure. Therefore, geometric and registration techniques are developed to correct the geometrical distortion. Dynamic image processing and analysis techniques are applied to extract useful information, including 3D data, from these images. The extracted information is an important aid to diagnosis and visualization.